Mathematical Model on The Control of Intestinal Torsion in Pigs - Jafaar Olasunkanmi Lawal; Clapperton Enosakhare; Sylvester Oghenetobeyere Okpako (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
An institutional based research at Federal College of Education (Technical) Ekiadolor, Benin City, Edo State, Nigeria, examined a pig farm in the Ovia North East Local Government Area, investigating a mathematical model on the control of intestinal torsion in pigs through vaccination and fibre-rich nutritional feeds. It results in the application of a four-compartment mathematical model for pig intestinal torsion, which is made up of the classes S, I, V, and R for the Susceptible, Infected, Vaccinated and Recovered classes. This model is used to solve for the reproduction number (R0) using the Next Generation Matrix (NGM), to solve the positivity model, to solve for the existence and uniqueness of the model, and to plot the model graphs using Maple.
Keywords: Intestinal Torsion; Mathematical Model; Vaccination and Reproduction Number